ANALISIS KREATIVITAS GURU SD NEGERI 9 TA KECAMATAN TANETE RIATTANG KABUPATEN BONE DALAM PROSES PEMBELAJARAN IPAS - Sudarto, Sudarto; Asriadi, Asriadi; Sinta Pusvita Sari (Bajang Institute, 2025)
This research is a naturalistic qualitative research that aims to determine teacher creativity in the science learning process of SD Negeri 9 TA. The subjects in this study were the principal, grade V teachers. and grade V students of SD Negeri 9 TA. The data collection technique for this study was the interview techniques. The data analysis technique in this study was data reduction, data presentation and drawing conclusions. Based on the results of the data analysis, information was obtained that there are five aspects of teacher creativity in the science learning process. First, designing and preparing learning. Second, managing the class. Third, using a variety of methods. Fourth, utilizing learning media. Fifth, conducting an evaluation. So it can be concluded that teacher creativity in the science learning process has been carried out well. This is demonstrated through thorough preparation of teaching materials, conducive classroom management, use of varied learning methods, and evaluation. However, there are several aspects that still need to be improved, namely the utilization of learning media where teachers have not integrated technology into learning optimally